Antituberculosis: Synthesis and Antimycobacterial Activity of Novel Benzimidazole Derivatives - Yeong, Keng Yoon; Ali, Mohamed Ashraf; Tan, Soo Choon; Ismail, Rusli; Ang, Chee Wei; Kumar, Raju Suresh; Osman, Hasnah; Beevi, Farzana (Hindawi Publishing Corporation, 2013)
A total of seven novel benzimidazoles were synthesized by a 4-step reaction starting from 4-fluoro-3-nitrobenzoic acid under relatively mild reaction conditions.The synthesized compounds were screened for their antimycobacterial activity against M. tuberculosis H37Rv (MTB-H37Rv) and INH-resistant M. tuberculosis (INHR-MTB) strains using agar dilution method. Three of them displayed good activity with MIC of less than 0.2